PENGEMBANGAN KEMAMPUAN UMKM DALAM MEMPRODUKSI KONTEN VIDEO MELALUI CAPCUT SEBAGAI STRATEGI PEMASARAN DIGITAL DI MEDIA SOSIAL - Susanto, Eko Budi; Christianto, Paminto Agung; Darmawan, Wachid (Servirisma, 2025)
This Community Service (PkM) activity was carried out with the aim of improving the skills of Micro, Small, and Medium Enterprises (MSMEs) in Setono Village in producing and editing promotional videos using the CapCut application. In today's digital era, the ability to create interesting video content is an important asset for MSMEs in marketing their products. This workshop managed to attract 40 participants, exceeding the initial target of 30 participants, which shows the high enthusiasm of MSMEs to improve their digital skills. The materials presented include the basics of creating video content, effective shooting techniques, introduction and tutorials on using the CapCut application, and product branding strategies to increase sales. The results of the post-test and direct practice showed that participants had understood and were able to apply video editing skills using CapCut. Although face-to-face discussion sessions were limited, interaction and consultation continued through personal communication. This activity is expected to make a significant contribution to increasing the competitiveness of MSMEs in Setono Village through the use of social media as a means of promotion. The success of this program was supported by the enthusiasm of the participants and the relevance of the material to the needs of MSMEs in the digital era.